PEMAHAMAN PLURALISTAS ULAMA DAYAH DAN DAMPAKNYA TERHADAP PEMIKIRAN ISLAM DI ACEH - Muhammad Anzaikhan (Prodi Studi Agama-Agama, 2021)
Plurality is understood as religious diversity in a society that is increasingly disturbing and undergoing friction. The Dayah clerics in Aceh view plurality as sunnatullah, but the plurality that is recognized is only limited to religious tolerance in the eyes of the syafii school. The research method in this study is field research with a qualitative approach. Data was collected by interviewing Tengku Dayah and campus intellectuals. In addition, data support was also carried out in the form of a literature study on the basis of the thoughts of figures related to Ulama Dayah and Islamic thinkers in Aceh. The results of the study concluded that the majority of Ulama Dayah rejected the plurality of sects more than the rejection of religious plurality. The Ulama Dayah contradicted and even forbade the congregation and their students from studying Islamic Thought. As a result, the treasures of Islamic thought in Aceh are hampered and can only be lived within the academic scope of the campus. If Islamic thinkers appear among the dayah, then they must contextualize according to the understanding and pattern of the Sunnah, otherwise Islamic thinkers will be rejected and even expelled from the majority congregation in Aceh.